Implementasi Sistem Manajemen Risiko Berbasis ISO 31000:2018 dalam Pengelolaan Risiko pada Katering Sekolah Non-MSG Dapur Vani - Putri Dewi Renggani; Amelia Rahmadani; Aisyah Humayyrah; Lailafitri Pratiwi Kadmadi; Alfiana (Indo Publishing, 2025)
Non-MSG catering is increasingly popular because it offers more natural, safe, and healthy food, especially for children who require nutritional intake without excessive use of additives. These advantages make non-MSG catering more valuable in providing food that meets the nutritional needs of school children. However, despite its good food quality, most catering businesses still lack structured risk management and tend to rely on experience to address operational challenges. Dapur Vani, a non-MSG catering business, has implemented basic risk management efforts, but has not adhered to standard standards. Therefore, this study focuses on the implementation of an ISO 31000:2018-based Risk Management System to strengthen risk control in operational processes. The study used qualitative descriptive methods through observation, interviews, and documentation. Field findings indicate that the most frequent risks include human error in the production process, delays in raw materials, and late deliveries. Overall, catering businesses also face potential risks related to finances, service quality, compliance, occupational safety, and reputation. Through the implementation of the ISO 31000 process, these risks can be identified and managed more systematically and comprehensively.